Simultaneous Versus Delayed Resection for Initially Resectable Synchronous Colorectal Cancer Liver Metastases: A Prospective, Open-label, Randomized, Controlled Trial. Issue 1 (January 2021) - Boudjema, Karim; Locher, Clara; Sabbagh, Charles; Ortega-Deballon, Pablo; Heyd, Bruno; Bachellier, Philippe; Métairie, Sylvie; Paye, François; Bourlier, Pascal; Adam, René; Merdrignac, Aude; Tual, Christelle; et al.
Abstract : Objective: To answer whether synchronous colorectal cancer liver metastases (SLM) should be resected simultaneously with primary cancer or should be delayed. Summary Background Data: Numerous studies have compared both strategies. All were retrospective and conclusions were contradictory. Methods: Adults with colorectal cancer and resectable SLM were randomly assigned to either simultaneous or delayed resection of the metastases. The primary outcome was the rate of major complications within 60 days following surgery. Secondary outcomes included overall and disease-free survival. Results: A total of 105 patients were recruited. Eighty-five patients (39 and 46 in the simultaneous- and delayed-resection groups, respectively) were analyzed. The percentage of major perioperative complications did not differ between groups (49% and 46% in the simultaneous- and delayed-resection groups, respectively, adjusted OR 0.84, 95% CI 0.35–2.01; P = 0.70, logistic regression). Complications rates were 28% and 13% ( P = 0.08, χ 2 test) at colorectal site and 15% and 17% ( P = 0.80, χ 2 test) at liver site, in simultaneous- and delayed-resection groups, respectively. In the delayed-resection group, 8 patients did not reach the liver resection stage, and this was due to disease progression in 6 cases. After 2 years, overall and disease-free survival tended to be improved in simultaneous as compared with delayed-resection groups ( P = 0.05), a tendency which persisted for OS after a median follow-up of 47 months. Conclusions: Complication rates did not appear to differ when colorectal cancer and synchronous liver metastases are resected simultaneously. Delayed resection tended to impair overall survival. Abstract : Supplemental Digital Content is available in the text